PSIKOEDUKASI MELATIH DAYA INGAT DAN FOKUS ANAK DENGAN MUSIK MELALUI AKTIVITAS GERAK DI TK IT FATHIYYAH PALEMBANG - Mutia Mawardah; Bella Maryati (Bajang Institute, 2023)
This writing (implementation) aims to train children's memory and focus, develop children's learning potential as well as to understand the relationship between movement and provide appropriate stimulation to develop children's learning abilities. The implementation technique used is to make observations at TK IT Fathiyyah, Seberang Ulu II District, Palembang. The conclusion from this writing/implementation is that the existence of real work lectures will help children to train their memory and focus through psychoeducational games with music through movement activities. And help teachers pay more attention to the stimulus given to children so that their feelings don't get bored, and increase their enthusiasm. With that children more easily accept the lessons given.